Clustering Data National Examinations based on Social Media Using K-Means Methods - Chandra Eko Wahyudi Utomo; Mochamad Hariadi; Surya Sumpeno (JAREE (Journal on Advanced Research in Electrical Engineering), 2020)
The development of social media as a source of data is now increasingly interesting to study. The social media studied in this research is Twitter. Twitter as one of the top-ranked social media among social media accessed by the people of Indonesia. People's behavior can be learned by collecting and processing data, one of which is people's sentiments or opinions about national examinations in Indonesia. Twitter user behavior in the form of their comments about the national exam in Indonesia. This study aims to analyze the public sentiments of social media users about the National Examination in Indonesia. Data is retrieved by crawling data via the Twitter API. The data needs to be preprocessed first and feature extracted using TF-IDF. However, because the text data on Twitter is unstructured and very diverse data (variety), the grouping stage must be done first. Grouping technique using K-Means Clustering on Spark. Spark clustering techniques are used to overcome the grouping of data on very large and complex amounts of data. From the clustering process using Spark it was found that the grouping process resulted in 3 clusters where elbow detection was found in the third cluster of the number of clusters between 2 and 50. The results of clustering in the form of 3 large groups were further processed (with classification techniques) to get a positive or negative sentiment comparison of social media user comments about the national exam. Furthermore, these results become recommendations and new knowledge about community behavior regarding Social Media-based National Exams.Keywords: clustering, K-Means, national exam, sentiment analysis, social media.